2014
DOI: 10.1371/journal.pone.0083923
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Photon Cell Killing Based on the Spatio-Temporal Clustering of DNA Damage in Higher Order Chromatin Structures

Abstract: We present a new approach to model dose rate effects on cell killing after photon radiation based on the spatio-temporal clustering of DNA double strand breaks (DSBs) within higher order chromatin structures of approximately 1–2 Mbp size, so called giant loops. The main concept of this approach consists of a distinction of two classes of lesions, isolated and clustered DSBs, characterized by the number of double strand breaks induced in a giant loop. We assume a low lethality and fast component of repair for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…We have developed a general framework of cellular radiation response characterised using cellular phenotypic characteristics that can produce predictions of a range of endpoints including DNA repair, genetic aberration, and cellular survival. While other models have sought to make use of similar mechanistic approaches to radiation response 16 17 18 35 58 59 , we believe this is the first such model to explicitly incorporate this range of underlying mechanistic processes and endpoints together with cell survival in a single model.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a general framework of cellular radiation response characterised using cellular phenotypic characteristics that can produce predictions of a range of endpoints including DNA repair, genetic aberration, and cellular survival. While other models have sought to make use of similar mechanistic approaches to radiation response 16 17 18 35 58 59 , we believe this is the first such model to explicitly incorporate this range of underlying mechanistic processes and endpoints together with cell survival in a single model.…”
Section: Discussionmentioning
confidence: 99%
“…It has thus to be understood as an effective model which allows to study some basic aspects of radiation action, as e.g. the general shape of dose-response curves [15], the impact of dose-rate effects [26] and the kinetics of DSB rejoining [25]. However, this strategy is in line with other modeling approaches as reported e.g.…”
Section: Representation Of Cell-cycle Effectsmentioning
confidence: 93%
“…However, these alternative mechanisms would fail to simultaneously explain other effects for which the concept of differential lethality between iDSB and cDSB has been demonstrated to have a high predictive power. For example dose-rate effects in the case of protracted photon irradiation can be explained by the temporal pattern of DSB induction [26], and the increased effectiveness of high-LET radiation can be explained by the microscopic, spatial DSB distribution pattern [14,27]. In both cases, even though the same total number of DSB might be induced, the variation of effectiveness can be traced back to the modification of the number of iDSB and cDSB, respectively, as a consequence of the variation in the temporal or spatial distribution pattern.…”
Section: Basics Of the Globle Approachmentioning
confidence: 99%
“…Indeed, measurements of DSBs by time-resolved microscopy showed that their number and repair kinetics vary in genetically identical cells, depending, for example, on cell cycle phase and repair pathways used [7,36]. Moreover, models of DSB induction by ionizing radiation suggest the existence of both simple and complex breaks that are repaired with differential kinetics [37,38]. Complex breaks are generated when DSBs cluster in chromatin loops.…”
Section: Excitability and Variation In Damage Strength Can Explain Hementioning
confidence: 99%